Cinema 2: The Time-Image - Deleuze, Gilles 1925-1995; Tomlinson, Hugh; Galeta, Robert (Minneapolis University of Minnesota Press, 1989)
This text continues the major reassessment of cinema begun in Deleuze's "Cinema I: The Movement Image." In this volume, Deleuze is concerned with the representation of time in film and with the cinematic treatment of memory, thought and speech.
Originally published in 1985
Keywords: Film; Philosophy